2006
DOI: 10.1111/j.1445-2197.2006.03921.x
|View full text |Cite
|
Sign up to set email alerts
|

Tumour Necrosis Factor: Implications for Surgical Patients

Abstract: Tumour necrosis factor alpha (TNF-alpha) is an inflammatory cytokine primarily produced by macrophages. It is a unique protein with contradictive properties; it has the ability to induce cellular death by apoptosis and oncosis, but can also induce cellular regeneration and growth. Genetic polymorphisms in TNFA have been associated with poor outcome in some surgical patients and this may provide a useful tool to screen for high-risk patients. Manipulating TNF-alpha levels in vivo may influence the progression o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 83 publications
0
9
0
2
Order By: Relevance
“…TNF is a mediator in the normal inXammatory pathway [6] and has bactericidal properties [7]. A previous study found that patients requiring revision of total joint replacement due to sepsis had higher levels of serum TNF-alpha compared to those undergoing aseptic revision arthroplasty [8].…”
Section: Introductionmentioning
confidence: 99%
“…TNF is a mediator in the normal inXammatory pathway [6] and has bactericidal properties [7]. A previous study found that patients requiring revision of total joint replacement due to sepsis had higher levels of serum TNF-alpha compared to those undergoing aseptic revision arthroplasty [8].…”
Section: Introductionmentioning
confidence: 99%
“…Ассоциация uPar с α5β1 индуцирует в интегрине появление дополни-тельного сайта для фибронектина в дополне-ние к связывающему rgd-сайту. недавно на uPar был идентифицирован сайт связывания с α5β1 во втором домене (130)(131)(132)(133)(134)(135)(136)(137)(138)(139)(140)(141)(142) [49].…”
Section: сигнализация урокиназыunclassified
“…ВкМ -внеклеточный матрикс Biochemistry aNd BiotechNology for moderN mediciNe с ее уровнем в контрольной группе, в то время как нанесение тканевого активатора плазми-ногена подобного эффекта не оказывало [130]. фактор некроза опухолей-α (tNf-α), выраба-тываемый моноцитами/макрофагами, нейтро-филами, а также структурными компонентами сосудистой стенки (гладкомышечными клет-ками и фиб робластами), является важным по-средником развития воспаления и вызывает образование и секрецию провоспалительных факторов (интерлейкин-10, кортикостероиды, простагландины) [131].…”
Section: рис 8 схема механизмов способствующих пролиферации клетокunclassified
“…If levels of this key regulator of the inflammatory response are too low, an inadequate immune response occurs. Conversely, if levels of TNFα are elevated in the absence of infection then chronic inflammation can develop (Guicciardi and Gores 2009; Khalil et al, 2006; Silke 2011; Goetz et al, 2004). TNFα is produced predominantly by lymphocytes and monocytes/macrophages (Khalil et al, 2006).…”
Section: Introductionmentioning
confidence: 99%